Lunar maps and astronomical careers in 17th-century Iberian Peninsula - Haddad, Thomás A.S. (Circumscribere International Journal for the History of Science, 2011)
After the quick incorporation of the telescope to astronomical research practices in the first decades of the 17th century, lunar cartography (or selenography) flourished admiringly. In a short time maps of the satellite appeared incorporating the representation codes typical of earth cartography. Two decisive moments in this process were the publication, in 1647, of Selenographia, by Protestant lawyer and astronomer J. Hevelius, of Danzig, and soon afterwards, of the lunar maps by Jesuits G.B. Riccioli and F.M. Grimaldi, of Bologna (as part of the former’s Almagestum Novum, published in 1651); the Jesuits’ maps defined a extraordinary stable visual language and toponymic standard for the moon. Before these landmarks, however, several other proposals for lunar cartographies were made to satisfy different functions and audiences. We suggest here that they may be typologically classified under two categories, one mainly concerned with toponymics and the determination of borders (derived from the first lunar maps by Englishman T. Harriot), and the other connected with topographical representations (heir to G. Galilei’s lunar illustrations). Then we examine two maps belonging to each of those traditions published in 1631 and 1645, respectively by Jesuit C. Bruno, in Lisbon (in his book Collecta astronomica ex doctrina etc.), and by Royal Cosmographer to the Spanish Crown M.F. van Langren, in Brussels (Plenilunii / Lumina Austriaca Philippica, loose-sheet). We suggest that their different cartographic strategies are intelligible through divergent paths (which nevertheless touch one another), the political context and the audiences they intended for their maps. The intellectual and professional path of Van Langren, added to his toponymic proposal baptizing 325 lunar accidents with the names of the Spanish Habsburgs and their allies, besides projecting a fantastic European geography on the moon, leaves no doubt that his map represented above all a way to conquest Philip IV’s favor by symbolically extending the borders of his empire. C. Bruno also sought Habsburgs’ favor through his ideas relating to longitude determination methods. His lunar chart and the work it is inserted in, however, represent an opportunity to obtain recognition among the Society of Jesus astronomers and a wide European litterati audience not directly related to his patronage strategies.